Tindak Pidana Pencucian Uang - Erna Dewi (PRANATA HUKUM, 2013)
Efforts to combat money laundering This has significance when seeing its impacts, among others, financial system instability, economic distortions and possible interference to control the amount of money in circulation, and the increased variety of criminal acts that make money (wealth) as it is known, various crime, whether committed by individuals or by corporations within the territory of a state and those carried across the borders of other countries increased.